Photothermally enhanced hollow gold nanopigment for water evaporation and sterilization achieved via a photothermal effect - Jeong, Sohee; Park, Jae Young; Kim, Ju Min; Kim, Younghun (Building and Environment, 2023)
Humidity management in indoor environments, achieved through the application of antimicrobial coatings, is an important and significant component that influences human behavior in such environments. Recently, nanotechnology has been widely used for humidity management in the construction industry, by improving and functionalizing existing materials. However, when a humidity control material or novel nanocoating agent was applied, the water removal rate from the walls, particularly the painted surface, was not good. Therefore, in this study, a photothermally enhanced hollow gold nanopigment was prepared as an indoor humidity controller with sterilization capabilities. The photothermal effect of metal nanoparticles caused by the localized surface plasmon resonance (LSPR) is essentially a light-heat conversion mechanism, in which heat is created around nanoparticles (NPs) owing to their light absorption. In this study, hollow gold nanoparticles (HAuNPs) were synthesized, and they demonstrated a comparatively high photothermal performance under near-infrared light (NIR) irradiation. Subsequently, they were blended with paint to test their suitability for pigment and heat-generation performance. In a water evaporation test, under NIR irradiation, water droplets (10 μL) on the surface of the HAuNPs@paint_8 wt% evaporated entirely after 180 s, with evaporation rates of 400 g/m2·h. In a photothermal sterilization test performed with Escherichia coli on a wetted painted surface, colony growth was noticeably reduced by approximately 99%. These findings demonstrate that the HAuNP nanopigment can be used in applications in which a particularly high temperature must be maintained continuously to prevent bacterial development and manage humidity.
Keywords: Gold nanoparticle; Gold Nanoparticles; Hollow gold nanoparticle; Humidity-control; Nano-pigments; Painted surfaces; Photo-thermal; Photothermal effects; Photothermally; Water evaporation; Hollow gold nanoparticle; Humidity control; Nano-pigment; Photothermal effect; Sterilization